Neonatal outcome of abnormal versus normal antenatal Doppler in high-risk pregnancies - Sasi, Navaneetha; Kariyappa, Pushpalatha; Sohail, Abdus Subhan; Naik, Jyothi; Seetharam Rao, Udayakumar (International Journal of Contemporary Pediatrics, 2022)
Background: Umbilical Doppler flow abnormalities occur in 6% of high-risk pregnancies. Preterm infants born with abnormalities in the umbilical artery Doppler waveforms is at a risk of various complications. The objective of this study were to understand and compare the neonatal outcome of normal verses abnormal antenatal Doppler. Methods: 100 newborns each with normal antenatal Doppler and abnormal antenatal Doppler, born to women with singleton pregnancies of 28 weeks and above, were enrolled for the study after taking informed written consent from the parents. All the newborns enrolled were followed up for various neonatal outcomes and complications. Results: Majority of fetal Doppler abnormalities were seen in mothers with PIH (50% verses 21%) and Intra uterine growth restriction (59% verses 29%) which was statistically significant. Majority of babies in abnormal Doppler group were delivered by LSCS compared to normal Doppler group (72% verses 36%). Neonates in the abnormal Doppler had more risk of becoming SGA (52% verses 24%), more risk of developing NEC (32% verses 18%) and thrombocytopenia (34% verses 17%). The need for longer duration of NICU stay (22 days verses 14 days) and need for mechanical ventilation were more in them (17% verses 7%) compared to normal Doppler group. Conclusions: Colour Doppler is a useful modality to predict fetal outcome in high-risk pregnancies. It allows better understanding of hemodynamic changes in feto-placental and utero-placental circulation and helps pediatrician to anticipate the complications and helps in early intervention and thus results in decreased neonatal morbidity and mortality.